The benefits of river indicators to assess the ecological status of IIUM Campus - Harun, Nor Zalina; Mansor, Mazlina; Abu Noh, Safiah (Malaysian Institute of Planners, 2017)
The concept of sustainable campus has emerged from the social, economic and environmental impacts due to anthropogenic activities around the world. One of the initiatives of sustainable campus is the application of ecological indicators. The indicators provide information about the current condition and early warning on the possible risks of environmental impacts to the campus environment. However, lack of understanding on the values of natural ecosystem in campus and the lack of proper planning has led to the depletion of natural ecosystem. The study seeks to examine river degradation in IIUM campus and to explore the benefits of river indicators towards achieving IIUM as an ecologically sustainable campus. Data were gathered using a qualitative approach involving three methods of data collection namely: (i) document analysis, (ii) semi-structured interview and (iii) site inventory. The finding reveals that the application of river channel morphology indicators is an important basis for physical planning in making a campus ecologically sustainable. Further analysis suggests that the suitable indicators to assess the condition of IIUM River are the river channel morphology indicators such as width, depth, channel pattern and slope ratio. The process of selecting the indicators are carried out based on six criteria of good indicators discussed in this study. The study concluded that the application of river channel morphology indicators is a critical process in physical planning of a sustainable campus as it contributes in preventing the loss of natural ecosystem and it offers a credible basis for creating a conducive place for campus residents. Keywords IIUM campus, sustainable, ecological indicator, river